Wetland conservation in Nepal: policies, practices, problems and possibilities - Poudel, BS (Banko Janakari, 2009)
Wetlands are among the most productive but threatened ecosystems on earth. Wetlands provide many benefits - environmental, economic and social - yet there is a limited assessment of these multiple values and therefore, have little attention in national accounts. Nepal has been transforming its resource management policies in favor of local people. This paper reviews existing policy framework and legal mechanisms involved in wetlands. There are several acts and regulations which have direct or indirect bearing on wetland conservation and management. It also discusses issues and possibilities of wetland management in Nepal. Finally, it recommends capacity building, wetland survey and inventory. Key words: Wetlands, policies, plans, acts, Ramsar, ecosystem, values doi: 10.3126/banko.v19i3.2205 Banko Janakari, Special Issue February 2009, 5-9